Channa Striata Extract As An Adjuvant Therapy of Chronic Obstructive Pulmonary DIsease - Forest Khan, Achmed; Lanti, Yulia; Oka Wardhani, Lusi (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Globally the incidence of chronic obstructive pulmonary disease (COPD) is rising for every year and approximately about 600 million people will suffer from COPD by 2050. As the important of medical therapy for COPD patient, Nutritional therapy is also important for helping the improvement of the quality of life COPD patients. East Borneo is the biggest production of Channa Striata province in Indonesia. As the way to improve the acceptability of Channa Striata in COPD patients, the extraction process is one of the way to improve the oral nutrition support for COPD patients. Objective : The aim of this research to understanding the macronutrient content, food safety and acceptability of Channa Striata extract from Mahakam river basin as an alternative adjuvant therapy for COPD patients. Research Methods/ Implementation Methods : . A Proximate and food safety analysis using analytical observational research from laboratory test results that compared by SNI and the regulation about internal medicine fluids as the traditional Indonesian herbal potion category. The organoleptic tests using hedonic quality test with a completely randomized design. The statistical analysis using Kruskal-Wallis and continued by Mann Whiteney either Friedman test for describing the best research treatment. Results : The macronutrient content of Channa Striata extract is able to meet the fine COPD diet criteria because of low carbohydrate content and high in protein content that almost 20%. Channa Striata extract is fulfil the food safety criteria according to BPOM regulations. Statistically, Channa Striata extract that produced by using local food ingredients from local fishermen in East Borneo has better acceptability than commercial products from the outside of East Borneo. Conclusion/Lesson Learned : Channa Striata extract that using local food ingredients is a good alternative of adjuvant therapy for COPD patients